Art education and its relationship to the development of creative thinking among learners (Journal of the College of Basic Education, 2022)
Our current era is witnessing a wide scientific and technological revolution that has been reflected in all fields of life, including education. The education process no longer aims at acquiring students a set of knowledge, skills, and attitudes as much as it aims at modifying and comprehensively and deeply changing the behavior of learners to become more capable of creativity to the utmost degrees and limits, and the researchers see The real problem lies in the shortcomings of the applied process and a clear departure from achieving the goal of creativity and artistic educational activities in its development, and based on this, the problem of the current research is determined by questions that represented as a whole the axis on which the idea of ​​the current study settled and the choice of title